Implementation of Family-Based Education to Improve Medication Adherence Among Older Adults with Hypertension: A Case Study at the Pengadangan Primary Health Center: Asuhan Keperawatan pada Pasien Hipertensi dengan Implementasi Edukasi Berbasis Keluarga dalam Meningkatkan Kepatuhan Pengobatan di Wilayah Kerja Puskesmas Pengadangan - Herli Astuti; Apriani Susmita (PT. Sentra Ilmiah Teknologi Mandiri, 2026)
Hypertension is one of the most prevalent non-communicable diseases and a major contributor to morbidity and mortality worldwide. Successful hypertension management is highly influenced by patients’ adherence to medication. However, medication adherence among older adults remains a challenge due to limited knowledge, low awareness of the importance of long-term therapy, and inadequate family support. Family-based education is a nursing intervention that can improve patients’ and families’ knowledge, strengthen family involvement, and enhance medication adherence among older adults with hypertension. To describe the implementation of family-based education in improving medication adherence among older adults with hypertension through nursing care at the Pengadangan Primary Health Center. This study employed a descriptive case study approach involving one older adult patient diagnosed with hypertension. Nursing care was carried out through the stages of assessment, nursing diagnosis, planning, implementation, and evaluation. The intervention was conducted over 3 × 24 hours, while data were collected through interviews, observations, physical examinations, and documentation. The main intervention consisted of family-based education regarding hypertension, medication adherence, a low-sodium diet, physical activity, routine health check-ups, and strengthening the family’s role in supporting the patient’s treatment. Prior to the intervention, the patient frequently forgot to take antihypertensive medication, had limited understanding of the importance of medication adherence, and received insufficient family support. Following three educational sessions, both the patient and family demonstrated improved knowledge of hypertension, increased adherence to the prescribed medication regimen, and greater family involvement in reminding the patient to take medication, accompanying routine health check-ups, and providing motivation throughout the treatment process. The patient’s blood pressure also decreased from 165/100 mmHg to 145/90 mmHg. The implementation of family-based education improved the knowledge of both the patient and family, enhanced medication adherence, strengthened family support, and contributed to better blood pressure control in an older adult with hypertension. This intervention may serve as an effective nursing strategy for managing hypertensive patients in primary healthcare settings.